SOFT POWER: TRAINING OF VET TEACHERS AND TRAINERS (RESULTS OF THE RUSSIAN-GERMAN COOPERATION) - E. Yu. Esenina; Hannelore Kress (Russian State Vocational Pedagogical University, 2017)
Introduction. Nowadays, in Russia the system of interaction between educational institutions and enterprises-employers in training of specialists is being built again after more than a twenty-year period of dissociation. Sharing experiences with other countries on networking and strengthening of education relations with production is very useful for establishing this process. The aim of the publication is to present the results of the Russian-German cooperation in the field of preparation of the qualified pedagogical staff for the system of vocational education as one of the key conditions for ensuring the proper quality of vocational education. Methodology and research methods. The methods involve the methodology of comparative research; methods of collecting empirical information; conceptual and terminological analysis, interpretation, modeling, and problem method. Results. The approaches to preparation of pedagogical staff of the VET system in Germany and Russia are revealed and compared. Specifics of the German model are shown: existence of several skill levels of teachers of vocational education, distribution of zones of their responsibility, variability of providers of additional education, its market nature and minimum participation in its regulation of the state. Features of the modern Russian theory and training experience of instructors of vocational training are described. Despite the existing distinctions of systems of professional education of two countries, the similarity of the Russian and German methods of vocational education is observed. The conclusion is drawn on a community of requirements imposed in Germany and Russia to category of the workers who are carrying out staff training for manufacturing sectors. It is confirmed by the German experts on the basis of the analysis of the standard «Teacher of Vocational Education, Professional Education and Additional Professional Education». Also, the standard was checked and compared to AEVO (the regulatory base defining federal requirements to instructors-teachers in Germany). Scientific novelty consists in justification of modern model of training for VET teachers and trainers. The model provides implementation of variable modular curricula of additional vocational education for VET teachers and trainers. The most fruitful Russian and German experience is integrated; the international requirements and advanced technologies are considered when creating the model of training. Practical significance. Except the model of training for VET teachers and trainers, the education guidance «Methods of Vocational Education» is worked out. The education guidance summary is outlined in the present article.